Fiqih Sexual in Pesantren: A Case Study of Sexual Education in Islamic Boarding Schools - Ana Andriani; Beny Wijarnako (Green Publisher Indonesia, 2025)
Sexuality education in pesantren has an important role in shaping the social life of adolescents and protecting them from sexual deviance. This study aims to identify the learning of sexual fiqh in pesantren which involves analyzing the literature and sources relevant to sexuality education in pesantren and how the book of Sexual Fiqh is presented as learning material in Mitahussalam Islamic boarding school. The results of the analysis show that learning fiqih sexual in pesantren is very important to answer the challenges faced by adolescents in context of sexuality, especially against adolescent sexual behavior. The approach used in this research is qualitative with a case study method. Data collection techniques through interviews, in-depth observation and documentation. Data analysis is done by data reduction data presentation. The conclusion of this research is that sexual education in the Miftahussalam Banyumas Islamic boarding school is comprehensive with strict system and is also carried out by way of habituation. Habituation is a practical way of forming and fostering morals. The habits carried out by students are the result of formation of the pesantren environment which is exemplified by the caregiver as an educator. In general, the method used in learning fiqh in Miftahulssalam Banyumas Islamic boarding school uses the bandongan method accompanied by discussion and question and answer which is strengthened by a deliberation system. The characteristic of Miftahulssalam Islamic boarding school is disciplined behavior of students because the rules are so strict, especially on matters relating to sexual behavior in a preventive form.